2017
DOI: 10.1158/0008-5472.can-16-2339
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic Cancer Progression Relies upon Mutant p53-Induced Oncogenic Signaling Mediated by NOP14

Abstract: Mutant p53 (mutp53) proteins promote tumor invasion and metastasis in pancreatic ductal adenocarcinoma (PDAC). However, the mechanism underlying sustained activation of mutp53 oncogenic signaling is currently unclear. In this study, we report that NOP14 nucleolar protein (NOP14) expression is upregulated in PDAC tumors and metastatic tissue specimens. NOP14 overexpression promoted cell motility, whereas NOP14 inhibition decreased invasive capacity of PDAC cells. In vivo invasion assays conducted on established… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 25 publications
0
32
0
Order By: Relevance
“…The inactivation of P53 seems to display at a late stage in the carcinogenesis of IPMN. A recent study demonstrated that NOP14 overexpression promoted cell motility, whereas NOP14 inhibition decreased invasive capacity of pancreatic adenocarcinoma cells via P53 mutation stability that was validated as a functional target of NOP14 (49). The NOP14/mutP53 axis suppressed P21 expression at both the transcriptional and post-transcriptional levels via induction of microRNA-17-5p in pancreatic adenocarcinoma cells (49).…”
Section: Current Practice and The Updates On The Genomic Fieldmentioning
confidence: 99%
See 1 more Smart Citation
“…The inactivation of P53 seems to display at a late stage in the carcinogenesis of IPMN. A recent study demonstrated that NOP14 overexpression promoted cell motility, whereas NOP14 inhibition decreased invasive capacity of pancreatic adenocarcinoma cells via P53 mutation stability that was validated as a functional target of NOP14 (49). The NOP14/mutP53 axis suppressed P21 expression at both the transcriptional and post-transcriptional levels via induction of microRNA-17-5p in pancreatic adenocarcinoma cells (49).…”
Section: Current Practice and The Updates On The Genomic Fieldmentioning
confidence: 99%
“…A recent study demonstrated that NOP14 overexpression promoted cell motility, whereas NOP14 inhibition decreased invasive capacity of pancreatic adenocarcinoma cells via P53 mutation stability that was validated as a functional target of NOP14 (49). The NOP14/mutP53 axis suppressed P21 expression at both the transcriptional and post-transcriptional levels via induction of microRNA-17-5p in pancreatic adenocarcinoma cells (49). We should mention that in IPMNs, the inactivation of P53, concomitant with the inactivation of the P16, are found in 20% of borderline tumors, 33% of the non-invasive carcinomas, in all the invasive carcinomas and in any adenoma (50).…”
Section: Current Practice and The Updates On The Genomic Fieldmentioning
confidence: 99%
“…As indicated by Zhou et al [47] , the NOP14 in pancreatic cancer cells is capable to promote motility, proliferation and metastatic capacity. According to the ndings of Du et al [48] , NOP14 primed tumor invasion and metastasis by improving the stability of mutp53 mRNA. By inhibiting the Wnt/ ÎČ-catenin pathways, NOP14 suppresses breast cancer [49].…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemistry (IHC) was conducted to measure SRC and RhoA expression as described previously (Du et al, 2017). In brief, paraffin-embedded tissue was pretreated at 65°C for 2 h, followed by deparaffinization using standard procedures.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…All animal procedures were performed as described previously (Du et al, 2017;He et al, 2015). The animal experiments were conducted in accordance with the national Animal Experimentation guidelines (D.L.116/92) upon approval of the experimental protocol by the Institutional Animal Experimentation Committee of Peking Union Medical College.…”
Section: Pc Cell-engrafted Tumor Mouse Modelmentioning
confidence: 99%